Insights from the Fragility, Conflict, and Migration Fragile Lives 2024 session on social protection and resilience in fragile contexts - Quisumbing, Agnes R.; Carrillo, Lucia (CGIAR System Organization, 2024)
During Fragile Lives 2024, held on October 1st and 2nd, the CGIAR Research Initiative on Fragility, Conflict, and Migration (FCM) hosted a session titled “Fragility, Conflict, and Migration.” This session showcased diverse research exploring social protection, resilience, and decision-making in fragile regions. Presentations by Kibrom Abay, Jordan Kyle, and Halefom Nigus highlighted how social assistance programs can be tailored to local contexts, the role of community leaders in aid distribution, and the mental health impacts of shocks and interventions. Furthermore, Khalid Siddig‘s presentation underscored the profound economic and poverty-related impacts of the ongoing conflict in Sudan, while outlining actionable recovery strategies including leveraging the resilience of the agricultural sector, strengthening social protection systems, and securing sustained external support as critical pathways toward rebuilding the country’s economy. Agnes Quisumbing and Ibrahim Elbadawi added valuable discussion, emphasizing the need for context-specific approaches and rigorous research in conflict-affected areas.